STANDAR KINERJA SUPERVISOR PADA HOUSEKEEPING DEPARTEMENT DI GRAND JATRA HOTEL PEKANBARU - Arvi Yani; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
General supervision is the direction and control to lower level employeesin an organization or group of people who carry out supervision activities in callwith the supervisor. Therefor, this research aims to determine the performancestandards of supervisors at housekeeping departement in Grand Jatra HotelPekanbaru and constrains faced in carrying out duties and responsibilities assupervisors at housekeeping departement. This research used quantitatifdescriptive method to examine the issues. Sample in this research was 6 peopletaken by using census sampling. The data collection techniques in this researchusing observation, quesionnaires, and interviews. Likert scale was usedmeasuring instrument to determine the interval. Based on the result of research,supervisors response about the implementation of supervisor performancestandard that is the ability to behave as a leader, ability to plan, coordinationability, directional ability, supervision ability, and evaluation ability. Overall, theperformance of the supervisors is considered high.Key word : Standard Performance, Supervisor, Housekeeping Departement,Grand Jatra Hotel Pekanbaru